Invasões múltiplas em meios porosos desordenados - Silva, Jorge Roberto Pereira da (2013)
In this dissertation, we investigate by means of numerical simulations geometrical and transport properties related with the invasion phenomena through disordered porous media in a very slow invasion regime, using two and three dimensions porous medias. Here, the porous media is modeling by means of a random structure, where each pore is represented by a random number comes from a uniform distribution. We assume that the invasion process occurs in the limit of very low viscous force, which means that the invasion process is controlled by capillary force. In this limit the invasion percolation model without trap is suitable. The new aspect incorporated here, consists basically of a multiple invasion process, where after the first invasion takes place only part of the structure of the porous, that was invaded previous, can be invaded again. We study, how the multiple invasion changes the fractal dimension of the invaded cluster. Estimated values for the fractal dimension of the invaded region reveal that the critical exponents vary as a function of the generation number G, i.e., where the number of times the invasion takes place. On base in numerical datas, we show the averaged mass M of the invaded region decreases with a power law as a function of G, M ∼ G{−β} , where the exponents β ≈ 0.59 (2D) and β ≈ 0.73 (3D). We also investigated, how the fractal dimension changes as a function of G, find that the fractal dimension of the invaded cluster changes from df = 1.89 ± 0.02 to ds = 1.22 ± 0.02 and df = 2.52 ± 0.02 to ds = 1.46 ± 0.02 for (2D) and (3D), respectively. These results confirm that the multiple invasion process follows a continuous transition from one universality class (nontrapping invasion percolation) to another (optimal path), furthermore these change are continuos for both dimensionality. Another aspect investigated, was the avalanche distribution in the invasion process. We analyzed how the distribution of avalanche changes as function of G, more precisely, how the multiple invasion process changes the exponent τ of the power law distribution. Regardless the values, we find that the behaviour of the exponents τ looks like the same for both dimensions studied. The exponents τ , initially change in a very slow way until reach a region, of certain value of G which depend on the dimension, they start to decrease in a deep way until reach the saturation value. The saturation value is close, for (2D), to one-dimension cas